Antecedents and outcomes of learning from and with entrepreneurial role models: A systematic literature review - Nauck, Daniel; Kitanovikj, Bojan; Herzog, Michael (Taylor & Francis, 2025)
The article discusses the current state of the literature on learning with and from entrepreneurial role models (ERMO) to support practitioners’ and policy makers’ capacity-building activities. Data was obtained from 42 studies on entrepreneurial learning, analyzed through a systematic literature review process. The results shows that research addresses primarily entrepreneurship education (EE) contexts, with only a few authors focusing on the postventure creation effects of entrepreneurial learning. In particular, understanding the impact of ERMO related to competencies is scarce, leaving opportunities for researchers, especially for long-term studies. Also, the role of non-formal learning after venture creation has been largely neglected in previous research. Our review provides insight into the discussion of ERMO in this context, identifies gaps, and encourages practitioners and policymakers to engage with the topic.
Keywords: Entrepreneurial ecosystem; Entrepreneurial learning; Entrepreneurial role model; Literature review; Entrepreneurship